Sisters - Steel, Danielle (London : Corgi Books, 2008)
During an annual Fourth of July family gathering, the lives of four sisters--Candy, a supermodel; Tammy, a TV producer; Sabrina, an ambitious lawyer; and Annie, an artist--are changed by tragedy as they come together to support one another.
Keywords: Sisters -- Fiction; Domestic fiction